First molecular identification of the transgene red fluorescent protein (RFP) in transgenic ornamental zebrafish (Danio rerio) introduced in Peru - Scotto, Carlos (2013)
In this paper the transgenic fluorescent red, orange and pink zebra fish (Danio rerio), found in local aquariums in Peru, were identified using the PCR technique to amplify the transgene RFP sea anemone belonging to Discosoma spp. The gene expression of the red fluorescent protein (RFP) transgene was found to determine different gradients-of-bioluminescence (shades in color) in each GMO fish analyzed. We performed sequence analysis of the two variants of the RFP along with six variants of the existing fluorescent protein GFP from the Genbank, this could help identify quickly if they are new genes or variants thereof as these novel fluorescent proteins may be introduced in aquatic GMO in the future. Thus, developing and improving biosecurity measures through its timely detection at the molecular genetic level.